2021
DOI: 10.3906/sag-2012-157
|View full text |Cite
|
Sign up to set email alerts
|

Differences in corpus callosum morphology between healthy adolescents and adolescents with migraine: a case control study

Abstract: Background/aim: This study objected to compare the measurements of corpus callosum substructures of adolescents with migraine and healthy adolescents. Materials and methods:In a case-control design, adolescents aged 12-18 years with the diagnosis of migraine and healthy control group had brain magnetic resonance imaging examination. The CC dimensions including anteroposterior length, truncus, genu and splenium widths of the case and control groups were measured and compared. Results:The sample consisted of 188… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…According to the MIDAS scale, the measured values of the CC trunk were significantly lower in the moderate and severe disability groups. Akin et al 11 reportedthat the measured values of the CC splenium and genu were smaller in adolescents with migraines compared to healthy adolescents. Demir et al 30 reported a statistically significant reduction in the CC volume when migraine patients and control groups were compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the MIDAS scale, the measured values of the CC trunk were significantly lower in the moderate and severe disability groups. Akin et al 11 reportedthat the measured values of the CC splenium and genu were smaller in adolescents with migraines compared to healthy adolescents. Demir et al 30 reported a statistically significant reduction in the CC volume when migraine patients and control groups were compared.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies on CC measurements in migraine patients. Although some authors noted the presence of a smaller CC in patients with migraine compared to controls, the role of the CC in the pathophysiology of migraine has not been fully understood 10,11 . A better understanding of the brain changes of patients with migraines will not only aid in diagnosis but may also help explain migraine pathophysiology, leading to the development of targeted anti-migraine therapies.…”
Section: Introductionmentioning
confidence: 99%